Rip current occurrence probability at selected recreational beaches along Pahang coastline - Hamsan, Muhammad Amirul Syafiq; Ramli, Muhammad Zahir; Mustapa, Mohd Zaini (2019)
Rip currents are known as greatest beach hazard and coastal drowning incident to swimmer, bather and public. Due to lack of continuous report incident in this country make it difficult to get the exact number of rip current related drowning death and rescue occurring along coastal zone. This study examined fatalities and rescued due to rip current incident along recreational beaches located at Pahang coastline. This study examines this problem using drowning data at beach reported from Malaysia Civil Defence Force Pahang (MCDF) by beach rescuer from 2006 to 2018. These data were checked, corrected and tally with the report from other agencies such as Royal Malaysia Police (Pahang) and Fire and Rescue Department (Pahang). In order to identify beach for rip currents assessment, beach classification method (Wright and Short, 1985) were used to identify for beaches that belong to rip currents characteristic accordingly. Using calculation method, five recreational beaches along Pahang coastline a preliminary assessment of rip currents hazard was carried out. In this study, the region of study areas were divided into three parts, north (Balok and Batu Hitam), centre (Teluk Cempedak) and South (Kempadang and Sepat) As result, three out of five recreational beaches are may become potential and develop rip currents.